1993
DOI: 10.1016/0735-1097(93)90393-f
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and socioeconomic status: Impact on the diagnosis of congenital heart disease

Abstract: Prevalence rates of specific cardiac defects vary among black, white and Mexican-American children, probably reflecting different genetic and environmental backgrounds. The timing of referral for pediatric cardiac care, however, was not related to ethnicity, median family income or household educational level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 11 publications
7
38
2
Order By: Relevance
“…The lower prevalence of coarctation of the aorta for NH-black and Hispanic infants compared with NH-white infants suggested in the literature 9,20,29 is seen in our data to occur only among Hispanic males and females compared with NH-whites and although present for both black males and females, not statistically significant. Although reports of lower prevalence of ventricular septal defect for NH-blacks and Hispanics compared with NH-whites 14 was also seen in our study, the magnitude of the decrease was similar for both male and female NH-black and Hispanic infants compared with NH-whites. Our finding of lower prevalence of atrioventricular septal defect for Hispanic females compared with NH-white females has not been previously reported.…”
Section: Original Articlessupporting
confidence: 62%
See 1 more Smart Citation
“…The lower prevalence of coarctation of the aorta for NH-black and Hispanic infants compared with NH-white infants suggested in the literature 9,20,29 is seen in our data to occur only among Hispanic males and females compared with NH-whites and although present for both black males and females, not statistically significant. Although reports of lower prevalence of ventricular septal defect for NH-blacks and Hispanics compared with NH-whites 14 was also seen in our study, the magnitude of the decrease was similar for both male and female NH-black and Hispanic infants compared with NH-whites. Our finding of lower prevalence of atrioventricular septal defect for Hispanic females compared with NH-white females has not been previously reported.…”
Section: Original Articlessupporting
confidence: 62%
“…It is also possible that our results are due to racial/ethnic-sex differences in diagnosis of CHD after birth, but no published studies have documented differential access to diagnosis or care for infants with CHD. Although studies show racial/ethnic disparities in access to pediatric care and treatment received when care is obtained, [33][34][35] there are no statistically significant differences between blacks and whites in the age at diagnosis of CHD 36 and no reason to believe that, if present, this would occur differentially by sex; however, differential access to care could explain observed differences within sex groups.…”
Section: Original Articlesmentioning
confidence: 99%
“…Previously published studies reported no racial/ ethnic differences in age at referral to pediatric cardiology practices. 26,27 Of note in the current study, racial/ethnic disparities in neonatal mortality were 40% higher in NH-blacks and 26% higher in Hispanics compared with NH-whites. Race/ethnic differences in mortality could be due to variations in morphologic severity of the defect being greater among minorities, but to our knowledge, no studies have described such differences.…”
Section: Resultsmentioning
confidence: 93%
“…It has been proposed that racial disparities in mortality may be due to differences in access to medical care. In a population-based study of congenital heart disease patients born in Dallas County, Texas, in 1971 to 1984, Fixler et al 20 reported that the timing of referral for pediatric cardiac care was not related to ethnicity, median family income, or household education. Chang et al, 21 using data from hospital discharges for 1995 to 1996 in California, found no difference between whites, blacks, and Asians in age at operation for congenital heart disease.…”
Section: Fixler Et Al Five-year Mortality Of Functional Single Ventriclementioning
confidence: 99%